(untitled) (Innovaciones Educativas, 2019)
In this essay there is a discussion about some contributions that neuromarkting can provide for the care of older adults, in schools where an educational offer is offered to this population. As part of the arguments that support this text, it is stated that neuromarkting, being focused on neurological and cognitive processes, would serve as a tool to attract and retain older adults.